1997
DOI: 10.1097/00000539-199708000-00025
|View full text |Cite
|
Sign up to set email alerts
|

Safe Epidural Analgesia in Thirty Parturients with Platelet Counts Between 69,000 and 98,000 mm-3

Abstract: Regional anesthesia is a popular form of pain relief for the management of labor and delivery. Thrombocytopenia is considered a relative contraindication to the administration of regional anesthesia. Some authorities have recommended that an epidural anesthetic be withheld if the platelet count is <100,000 mm(-3). For the period of March 1993 through February 1996, we reviewed the charts of all parturients who had a platelet count <100,000 mm(-3) during the peripartum period. Eighty women met this criterion. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0
3

Year Published

2000
2000
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(39 citation statements)
references
References 12 publications
0
36
0
3
Order By: Relevance
“…Beilin, et al in their retrospective review reported safe epidural analgesia in thirty parturients with platelet counts between 69,000 and 98,000 per microliter [9].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Beilin, et al in their retrospective review reported safe epidural analgesia in thirty parturients with platelet counts between 69,000 and 98,000 per microliter [9].…”
Section: Discussionmentioning
confidence: 99%
“…Very few cases were associated with thrombocytopenia alone [8][9][10]. Different causes of thrombocytopenia may have different risks of bleeding.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…77 A PC of 50,000·µL -1 is sufficient for spinal anesthesia whereas a minimum PC of 80,000·µL -1 has been proposed for epidural anesthesia. [78][79][80][81][82] It may be difficult to assess the effectiveness of platelet transfusions. One platelet concentrate usu-ally produces an increase of about 7,000 to 10,000 platelets·mm -3 one hour after transfusion in a 70-kg adult.…”
Section: Risk Of Perioperative Bleeding If Antiplatelet Medications Amentioning
confidence: 99%
“…4,[12][13][14][15] More information is needed to determine the safety of epidural analgesia in the presence of thrombocytopenia. Investigations have shown that the bleeding time does not predict bleeding in remote sites (e.g., the epidural space) and its use has dropped significantly.…”
Section: Patient Education and Consent For Labour Analgesiamentioning
confidence: 99%